MODEL KOOPERATIF WHO AM I MENGGUNAKAN ZOOM MENDORONG LITERASI ANAK DALAM PEMBELAJARAN DARING - Agung Prihatmojo (Edukasi Lingua Sastra, 2021)
Abstract: Technological advances can help learning during the Covid-19 pandemic. The development of internet-based technology provides zoom video conference applications. The use of zoom helps teachers and students in virtual face-to-face interactions separated by space and distance. The Who Am I cooperative model uses zoom meetings to stimulate student literacy in online learning so as to increase literacy during the Covid 19 pandemic. Literacy stimulation is an inner drive (without coercion) to carry out reading and writing activities. Who Am I model that uses game tournaments as a learning-while-playing strategy. Learning while playing is able to provide a good stimulus for literacy activities. The characteristics of the Who Am I learning model provide a stimulus to literacy. These characteristics are: 1) learning in groups, 2) learning while playing, 3) fun learning, 4) learning vocabulary mastery.